El Manicomio General La Castañeda en México. - Andrés Ríos Molina (Nuevo mundo - Mundos Nuevos, 2009)
This paper analyzes the clinical files from two inmates in the General Insane Asylum La Castañeda (Mexico City) during the Revolution (1910-1920). It exposes three aspects: First, the methodological problem that this kind of files present. Secondly, it analyzes the social relations and the cultural context of both cases. Third, it exposes the value of this kind of clinical files for the history of psychiatry and culture.